Reading and Writing as Academic Literacy in EAP Program of Indonesian Leaners - Solikhah, Imroatus (Dinamika Ilmu: Jurnal Pendidikan, 2015)
This study investigates academic literacy imposed in reading and writing for academic purposes in the EAP program. This study uses descriptive design elaborating data from curriculum documents and interviews.Â  Involving 45 participants from IAIN Surakarta and Veteran University, data were analyzed using constant-comparison and inductive analysis tecniques. The study diseovers that academic literacy is prominent to serve and recently it has been the growing learning outcomes universities should provide besides discipline and experise. Academic literacy in EAP program is embedded into academic vocabulary, grammar, reading and writing for academic purposes.Â  Consequently, academic literacy should be incurred in the curriculum, syllabus, aims and objectives, and teaching materials.